Perancangan E-Photobook Arsitektur Candi di Malang sebagai Media Informasi Wisata - Rina Nurfitri; Chaulina Alfianti Oktavia; Rifdatus Noviana Bilqis (MAVIS : Jurnal Desain Komunikasi Visual, 2025)
Malang is an area in East Java that is rich in tourist destinations and historical heritages, including temples (candi) with Hindu and Buddhist characteristics. However, public awareness of the existence of these temples is decreasing, especially among teenagers. Based on a survey, many teenagers aged 19–25 years do not know the number or location of the temples in Malang. Therefore, this research aims to design an e-photobook of temple architecture in Malang as a tourism information medium that can provide a deeper understanding of this cultural heritage. Temples possess distinct historical and architectural values, functioning as places of worship and religious rituals. This e-photobook uses an architectural photography approach to document the beauty and structural details of the temples. The design method uses Design Thinking with data collection techniques involving observation, interviews, and literature study. The design process includes digital layout and photography techniques, using Adobe Photoshop and Adobe InDesign. Five main temples are the objects of this research: Candi Singosari, Jago, Kidal, Badut, and Sumberawan. Some of the architecture of these temples has not been well visualized digitally. With a temple book in a more accessible digital format, this e-photobook is expected to become a reference for tourists as well as increase public awareness of the importance of preserving temples as part of Indonesia's cultural heritage.